Marriage as a covenant : a study of biblical law and ethics governing marriage, developed from the perspective of Malachi - Hugenberger, Gordon Paul. (Vetus Testamentum, Supplements, 1994)
This book focuses on the interpretation of Malachi 2:10-16, which censures the lax marital practice of its contemporaries. In particular, Hugenberger investigates Malachi's identification of marriage as a \'covenant\' in response to recent scholarly challenges to this identification. Taking the issues raised by Malachi as his point of departure, Hugenberger examines the nature of covenant and oath (including verba solemnia and oath-signs), and, in light of these findings, explores the theory of marriage implied elsewhere in the Old Testament. Included in this investigation are an analysis of the concentric literary structure of Malachi and a study of the Old Testament's ethical perspectives on divorce, polygamy, and sexual fidelity. An extensive bibliography and indices complete the book.